Estimation of future water resources of Xiangjiang River Basin with VIC model under multiple climate scenarios - Guo-qing Wang; Jian-yun Zhang; Yue-ping Xu; Zhen-xin Bao; Xin-yue Yang (Water Science and Engineering, 2017)
Variation trends of water resources in the Xiangjiang River Basin over the coming decades have been investigated using the variable infiltration capacity (VIC) model and 14 general circulation models' (GCMs') projections under the representative concentration pathway (RCP4.5) scenario. Results show that the Xiangjiang River Basin will probably experience temperature rises during the period from 2021 to 2050, with precipitation decrease in the 2020s and increase in the 2030s. The VIC model performs well for monthly discharge simulations with better performance for hydrometric stations on the main stream of the Xiangjiang River than for tributary catchments. The simulated annual discharges are significantly correlated to the recorded annual discharges for all the eight selected target stations. The Xiangjiang River Basin may experience water shortages induced by climate change. Annual water resources of the Xiangjiang River Basin over the period from 2021 to 2050 are projected to decrease by 2.76% on average within the range from −7.81% to 7.40%. It is essential to consider the potential impact of climate change on water resources in future planning for sustainable utilization of water resources.